Improving gross motor skills of children through traditional games skills practiced along the contextual interference continuum - Hussain, Bahar; Cheong, Jadeera Phaik Geok (Frontiers in Psychology, 2022)
Gross Motor Skills are the foundation for humans reaching an optimum level of motor competence necessary to undergo normal development, maintain health, and achieve athletic excellence. Yet, there is evidence that gross motor skill levels of children are on a decline globally. Therefore, the main purpose of this study was to investigate the effectiveness of Traditional Cultural Games skills, practiced according to different amounts of contextual interference, on the acquisition and retention of gross motor skills. A total of 103 Pakistani primary school children aged between seven and 10 years were recruited for this study. Participants were randomly assigned to four practice groups with different amounts of contextual interference: block (low interference), gradually increasing (moderate interference), random (high interference), and game-based (high interference). The Test of Gross Motor Development (TGMD-2) was used to assess four tasks (overhead throw, underhand throw, catch, and throwing to a target). The test was administered on four occasions: during pre-test, posttest, retention, and transfer. The results showed that the Random group outperformed all the other groups in the posttest and the retention test. Meanwhile, in the transfer test, both Random and Game-Based groups performed better than the Block and Gradually Increasing groups. There were no differences between the Random and Game-Based groups during transfer. Practicing Traditional Cultural Games skills according to a random order was better for the acquisition and learning of Gross Motor Skills. The contextual interference effect was evident, whereby high interference practice schedules were superior to low and moderate interference practice schedules.